2021
DOI: 10.1007/s11440-021-01169-x
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling of rainfall-induced slope failure in variably saturated soil

Abstract: This paper presents the results of centrifuge tests on rainfall-induced instabilities in variably saturated slopes. The roles of rainfall intensity and initial conditions, such as slope angle, porosity and degree of saturation of the soil, in the failure initiation and postfailure kinematics are considered. The failure patterns, infiltration profile and deformation at prefailure and postfailure stages are characterized. The results indicate that rainfall-induced slope failures usually follow one of the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…With increasing velocity, the granular mass gradually flowed in a more ordered manner as a viscous fluid as it entered the fluid phase, with a coordinated flow‐like velocity distribution, that is, the Bagnold profile. Such fluidized behavior is generally attributed to a shear‐induced positive pore pressure (Iverson et al., 2011; Okura et al., 2002; Take & Beddoe, 2014; Wang et al., 2021). However, no fluctuation of pore pressure was evident in this physical experiment (Figures 5m–5o).…”
Section: Resultsmentioning
confidence: 99%
“…With increasing velocity, the granular mass gradually flowed in a more ordered manner as a viscous fluid as it entered the fluid phase, with a coordinated flow‐like velocity distribution, that is, the Bagnold profile. Such fluidized behavior is generally attributed to a shear‐induced positive pore pressure (Iverson et al., 2011; Okura et al., 2002; Take & Beddoe, 2014; Wang et al., 2021). However, no fluctuation of pore pressure was evident in this physical experiment (Figures 5m–5o).…”
Section: Resultsmentioning
confidence: 99%
“…Note that an attempt is not made to study the failure mechanism of the slope under rainfall conditions. This regard is explored in our companion paper [18]. Instead, we are focusing on the performance of the rainfall device.…”
Section: Application: Rainfall-induced Slope Failurementioning
confidence: 99%
“…In recent years, experimental methods and numerical simulation methods have been applied to study the stability of slope under the rapid change of reservoir water level or rainfall. Based on centrifuge tests on rainfall-induced instabilities in variably saturated slopes, Wang et al indicated that rainfall-induced slope failures usually follow the slide-to-flow or flowslide failure modes [13]. Song et al have investigated the influence of rapid water drawdown on the seismic response characteristics of a reservoir rock slope by using numerical dynamic analyses and shaking table tests [14].…”
Section: Introductionmentioning
confidence: 99%